The people's artist Prokofiev's Soviet years - Morrison, Simon Alexander 1964- (Oxford Univ. Press, 2010)
This is a detailed chronicle of Prokofiev's career from 1932 to 1953, based on exclusive and extensive research conducted at several Russian archives. The book examines Prokofiev's decision to relocate to Stalin's Russia in 1936 and the composer's aesthetic and spiritual views.
Keywords: Prokofiev, Sergey -- 1891-1953; Prokofʹev, Sergej Sergeevič -- 1891-1953; Geschichte 1918-1953; Composers -- Soviet Union -- Biography; Sowjetunion; Biografie